Tournament incentives and IPO failure risk - Colak, Gonul; Gounopoulos, Dimitrios; Loukopoulos, Panagiotis; Loukopoulos, Georgios (Journal of Banking & Finance, 2021)
This study tests the proposition that higher tournament incentives play a major role in lowering the failure risk of Initial Public Offerings (IPOs). Measuring tournament incentives as the pay gap between the CEO and its subordinate executives, we find that an interquartile change in the distribution of the CEO pay gap translates into a decline in failure risk probability by approximately 27%. The results are driven by the long-term rather than the short-term component of exective pay. Our results hold in an instrumental-variable setting that exploits exogenous variation in the likelihood of employing intra-firm, tournament-based, promotion incentives. Cross-sectional tests indicate that the negative link between tournament incentives and IPO failure is more pronounced when internal promotion contests are more likely to occur. Finally, we document that CEO pay gap is associated with superior long-run operating performance and greater investment efficiency.